Studi Desain Disposal Dan Perhitungan Kapasitas Out Pit Dump 3 Kabupaten Barito Selatan Provinsi Kalimantan Tengah: Disposal Design Study and Capacity Calculation of Out Pit Dump 3 in South Barito Regency, Central Kalimantan Province - Rachman, Muhammad Fathur; Nurwaskito, Arif; Thamsi, Alam Budiman (Journal of Engineering Science and Technology Applications, 2025)
Disposal is an area designed and planned to accommodate overburden material from mining activities. The objective of this study is to create a disposal design and determine its design volume capacity. The research methodology applies a technical approach, such as processing topographic data as the basis for design, utilizing the situational map of the disposal area as a reference, and considering production targets. Based on the conducted study, a disposal design was developed from the lowest to the highest elevation, starting from the requested elevation of 80 up to the peak design at elevation 120. The calculation of the design volume capacity resulted in a total of 11,410,645 Bcm, obtained from each design stage by elevation.